Can Technical Assistance Sow the Seeds for Rural Finance? - Bruhn, Miriam; Reddy, Rekha; Ruiz Ortega, Claudia (World Bank, Washington, DC, 2018)
Government interventions to lower interest rates and expand credit to the rural sector are common in developing countries. Some of these policies, like interest rate subsidies, though well-intentioned, can be distortionary and achieve opposite results. Interventions that tackle constraints that prevent the market from allocating credit on its own may achieve better results. One such constraint often present in rural areas is lack of technical capacity. Rural financial institutions are often ill-equipped to screen, monitor and manage risk and to price products. This lack of capacity increases operational costs which are passed on to borrowers in the form of higher interest rates and less lending.